2010
DOI: 10.1007/s11136-009-9580-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life among paediatric survivors of primary brain tumours and acute leukaemia

Abstract: Evaluation of HRQL should be treated as an additional independent parameter in an assessment of the long-term results of oncological treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 31 publications
4
50
3
2
Order By: Relevance
“…The clinical importance of this small difference is therefore questionable. However, our findings are in line with findings from other studies that described impaired HRQoL in similar domains, using other HRQoL measures [9,10,[19][20][21]. The reduced HRQoL on the Motor and Cognitive functioning scales can be explained by the high proportion of neurologic impairments seen in these children.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The clinical importance of this small difference is therefore questionable. However, our findings are in line with findings from other studies that described impaired HRQoL in similar domains, using other HRQoL measures [9,10,[19][20][21]. The reduced HRQoL on the Motor and Cognitive functioning scales can be explained by the high proportion of neurologic impairments seen in these children.…”
Section: Discussionsupporting
confidence: 92%
“…Monitoring of health-related quality of life (HRQoL) is done, for example, in childhood survivors who are treated for a pilocytic astrocytoma [9][10][11], low-grade glioma [12], high-grade glioma [13], craniopharyngioma [14,15], medulloblastoma [16,17], and in heterogeneous groups [18][19][20][21][22][23][24]. In most of these studies, survivors reported a variety of degree of reduction in HRQoL compared with healthy age mates [9,10,[13][14][15][16][18][19][20][21][22][23][24]. This could be explained by the heterogeneity of brain tumors and their treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the tumor histology may favor a better prognosis, and a better overall QOL in pediatric LGG patients. Studies have reported that pediatric patients with CNS tumors have overall lower QOL than pediatric patients undergoing leukemia treatment [8, 9]. In contrast, the current study population reports higher QOL functional scores in comparison to adult long-term survivors of acute myeloid leukemia (AML).…”
Section: Discussionmentioning
confidence: 63%
“…Reports assessing QOL in pediatric patients have demonstrated lower overall QOL in children with CNS tumors compared to their healthy counterparts [9, 18]; however, those patients were either undergoing or within one year of treatment completion, while the majority of the participants in this study were several years post treatment. In comparison to previously published reports of adult patients with LGGs, the current study of adult survivors of pediatric LGGs appear to have better overall QOL scores.…”
Section: Discussionmentioning
confidence: 95%
“…The HRQOL of oncologic paediatric patients has been the focus of many studies and is seen to be lower in patients under treatment and who have survived cancer as compared to the healthy population (Pogorzala et al, 2010;Ribi et al, 2005;Speechley, Barrera, Shaw, Morrison, & Mounse, 2016). The measurement of HRQOL in clinical practice represents a tendency to consider the health of patients in their entirety.…”
mentioning
confidence: 99%